2006
DOI: 10.1037/1040-3590.18.3.250
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the latent structure of the MMPI-2 F(p) scale in a forensic sample: A taxometric analysis.

Abstract: P. A. Arbisi and Y. S. Ben-Porath (1995) originally proposed that the Infrequency Psychopathology scale, F(p), be used as the final step in an algorithm to determine the validity of a Minnesota Multiphasic Personality Inventory-2 (MMPI-2) protocol. The current study used taxometric procedures to determine the latent structure of F(p) among examinees with profiles that would necessitate the interpretation of F(p) when using Arbisi and Ben-Porath's proposed algorithm. Participants included a subsample of 289 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 34 publications
2
24
2
Order By: Relevance
“…The taxonic results obtained by Strong et al (2006) and Frazier et al (2007) clash with the dimensional results of and the current study. One possible explanation for these discrepant findings is that sampling or procedural factors created a pseudotaxon in the Strong et al (2006) and Frazier et al (2007) studies.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The taxonic results obtained by Strong et al (2006) and Frazier et al (2007) clash with the dimensional results of and the current study. One possible explanation for these discrepant findings is that sampling or procedural factors created a pseudotaxon in the Strong et al (2006) and Frazier et al (2007) studies.…”
Section: Discussionsupporting
confidence: 87%
“…One possible explanation for these discrepant findings is that sampling or procedural factors created a pseudotaxon in the Strong et al (2006) and Frazier et al (2007) studies. A second possibility is that both sets of studies produced valid results but that contextual factors led to divergent outcomes.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Studying the latent structure of individual differences in response distortion would provide an empirical basis for selecting between these approaches. Similar problems in the realm of clinical assessment have led to taxometric studies (e.g., Strong et al, 2006) that suggest that symptom overreporting may be a categorical phenomenon.…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, structural studies have found a categorical difference between respondents scoring at high and low levels on the Minnesota Multiphasic Personality Inventory (MMPI) infrequency scale F and the MMPI infrequency scale F(p); these scales are used to detect symptom overreporting (e.g., Strong, Glassmire, Frederick, & Greene, 2006). This finding suggests the utility of developing techniques to assign individuals to groups-those who do and those who do not overreport their symptoms -rather than assessing overreporting as a dimensional construct.…”
Section: Why Distinguish Categories and Dimensions?mentioning
confidence: 99%